2010
DOI: 10.1007/s10554-010-9657-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myocardial fibrosis by endoventricular electromechanical mapping in experimental nonischemic cardiomyopathy

Abstract: Cardiac fibrosis plays an important prognostic role in nonischemic cardiomyopathy (NICM), making it a potential therapeutic target. Although electromechanical mapping has been used to identify myocardial scar and facilitate intramyocardial intervention in the setting of ischemic heart disease, its application has not been described in NICM. We assessed the detection of myocardial fibrosis by endoventricular electromechanical mapping in an experimental model of NICM. The NOGA® XP system was used to perform left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…However, all interventions were associated with elevations in serum troponin-T, indicating that early myocardial injury may have been caused by the injection process itself or by the cryopreservant agent that was common to both groups. Although the long-term consequences of injection site injury/inflammation are difficult to ascertain, the burden of fibrosis in placebo-injected animals was consistent with the level that we have previously noted in other doxorubicin NICM sheep (21). Effects of MPC in experimental NICM.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, all interventions were associated with elevations in serum troponin-T, indicating that early myocardial injury may have been caused by the injection process itself or by the cryopreservant agent that was common to both groups. Although the long-term consequences of injection site injury/inflammation are difficult to ascertain, the burden of fibrosis in placebo-injected animals was consistent with the level that we have previously noted in other doxorubicin NICM sheep (21). Effects of MPC in experimental NICM.…”
Section: Discussionsupporting
confidence: 88%
“…However, corresponding results in large animal or clinical studies have thus far been lacking. Therefore, in the present study, we evaluated MPC therapy in an ovine model of anthracycline-induced cardiomyopathy that consists of reproducible, moderate-severe LV dysfunction, with extensive cardiomyocyte, small-vessel and Purkinje fiber injury and increased myocardial fibrosis (19,21). Transendocardial cell delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Consistent with the findings of preclinical studies, 15 we found significant heterogeneity of myocardial viability and contractile dysfunction in patients with DCM. In our study, we chose the viable regions with the greatest perfusion defect or greatest decrease in linear shortening to target the region of interest, theoretically maximizing the response to stem cell therapy.…”
Section: Vrtovec Et Al Stem Cell Delivery In Dilated Cardiomyopathy S47supporting
confidence: 85%